2014
DOI: 10.1007/s11273-014-9399-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an integrated peat-harvesting and reclamation method: peatland-atmosphere carbon fluxes and vegetation recovery

Abstract: We document a two-year experimental trial of a recently-developed integrated peat-harvesting and reclamation technique at a poor fen in northern Ontario, Canada. We removed and conserved the uppermost *0.3 m of peat in blocks while deeper peat was harvested from the resultant pit. We allowed the extraction pit to flood with shallow groundwater, and then reclaimed the conserved surficial peat blocks by transplanting them into the flooded pit where they formed a low, floating mat. In the 2nd year after harvest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The disruption of soil structure and microbial communities resets the ecological clock, thus reducing or eliminating the beneficial effects of time on soil biogeochemical processes (Janzen 2016). Several studies indicate that transplanting intact wetland soil and/or vegetation to wetland restoration or creation sites reduces GHG emissions, compared to common practices noted above (Wilhelm et al 2015;Murray et al 2017;Cagampan and Waddington 2008;Waddington et al 2009). Brown and Bedford (1997) found that transplanting intact blocks of wetland soil results in more successful establishment of wetland species, while reducing the presence of invasive plants during restoration of drained wetlands.…”
Section: Local and Project-level Strategies And Best Management Practmentioning
confidence: 99%
“…The disruption of soil structure and microbial communities resets the ecological clock, thus reducing or eliminating the beneficial effects of time on soil biogeochemical processes (Janzen 2016). Several studies indicate that transplanting intact wetland soil and/or vegetation to wetland restoration or creation sites reduces GHG emissions, compared to common practices noted above (Wilhelm et al 2015;Murray et al 2017;Cagampan and Waddington 2008;Waddington et al 2009). Brown and Bedford (1997) found that transplanting intact blocks of wetland soil results in more successful establishment of wetland species, while reducing the presence of invasive plants during restoration of drained wetlands.…”
Section: Local and Project-level Strategies And Best Management Practmentioning
confidence: 99%
“…Wilhelm et al . ) – on timescales of years to decades. Plant community structure and carbon sequestration in harvested peatlands can sometimes recover spontaneously in the decades that follow intensive harvesting without deliberate restoration efforts (Lavoie et al .…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that the transplanted acrotelm assisted the restoration by keeping the water table and moisture conditions favourable for Sphagnum growth when the acrotelm is replaced immediately or within a few days (Cagampan & Waddingston , ; Wilhelm et al. ). The restoration process on harvested peatland and our natural peatland disturbed by road construction also differs in other features than just storage time.…”
Section: Discussionmentioning
confidence: 99%